Вызовы современному русскому литературному языку - Медведев, Владимир (Studia Rossica Posnaniensia, 2020)
The article is devoted to the study of some active processes affecting the system of the modern Russian language. The result of the study is the identification of factors that negatively affect the dynamics of the Russian language, which are presented in socio-political and linguistic aspects. The socio-political reasons are caused by the active reduction of the Russian-language information space in the near and far abroad area under the influence of the collapse of the Soviet Union. Unsuccessful phenomena in the current state of the Russian language consist in the intentional violation of the language norms in the Internet space, the substitution of normative vocabulary for meaningfully and stylistically belittled expressions of rural life, the clogging of the Russian literary language with words and verbal turns of slang origin, the dissemination of obscene vocabulary, the saturation of the language with words and expressions of foreign origin, and the unjustified euphemization of speech, leading to the erosion of the meaning of words. The general conclusion is the need for the serious efforts of the whole society against the simplification and the purity of the Russian literary language.